The design, synthesis and structure-activity relationships associated with C28 amine-based betulinic acid derivatives as inhibitors of HIV-1 maturation. Issue 9 (15th May 2018) - Chen, Yan; Sit, Sing-Yuen; Chen, Jie; Swidorski, Jacob J.; Liu, Zheng; Sin, Ny; Venables, Brian L.; Parker, Dawn D.; Nowicka-Sans, Beata; Lin, Zeyu; Li, Zhufang; Terry, Brian J.; et al.
Graphical abstract: Abstract: The design and synthesis of a series of C28 amine-based betulinic acid derivatives as HIV-1 maturation inhibitors is described. This series represents a continuation of efforts following on from previous studies of C-3 benzoic acid-substituted betulinic acid derivatives as HIV-1 maturation inhibitors (MIs) that were explored in the context of C-28 amide substituents. Compared to the C-28 amide series, the C-28 amine derivatives exhibited further improvements in HIV-1 inhibitory activity toward polymorphisms in the Gag polyprotein as well as improved activity in the presence of human serum. However, plasma exposure of basic amines following oral administration to rats was generally low, leading to a focus on moderating the basicity of the amine moiety distal from the triterpene core. The thiomorpholine dioxide (TMD) 20 emerged from this study as a compound with the optimal antiviral activity and an acceptable pharmacokinetic profile in the C-28 amine series. Compared to the C-28 amide 3, 20 offers a 2- to 4-fold improvement in potency towards the screening viruses, exhibits low shifts in the EC50 values toward the V370A and ΔV370 viruses in the presence of human serum or human serum albumin, and demonstrates improved potency towards the polymorphic T371A and V362I virus variants.